ANALISIS PENURUNAN KADAR BESI (Fe) PADA AIR BERSIH DENGAN METODE MULTIPLE PLATFORM AERATOR DI PT. X (Politeknik Kesehatan Kemenkes Bandung, 2021)
The source of tap water in PT. Linico Indonesia is from groundwater. Iron (Fe) level in groundwater at PT. Linico Indonesia after checked is 6.11 mg/L and exceeds the quality standard. Then the groundwater treatment is carried out with the aeration process using the multiple platform aerator method. The purpose : to reduce iron (Fe) levels in groundwater and to determine the difference in platform height distances in the aeration process with the multiple platform aerator method with a platform height of 30 cm, 40 cm, and 50 cm. This type of research : experimental research with a pretest-posttest without control research design. The population : all of the groundwater used at PT. Linico Indonesia with sample size is 21,6 liters. The sampling technique is grab sampling. Collection data techniques : checking iron (Fe) level in laboratory, measurement temperature and pH of groundwater. Collection data instruments : spektrophotometer, thermometer for water, and pH meter. Research result : the average initial iron (Fe) content in groundwater is 6.11 mg/L. The average level of iron (Fe) in groundwater after the aeration process with a platform height distance of 30 cm is 3.29 mg/L with a percentage of 47.74%, 40 cm is 2.63 mg/L with a percentage of 54.79% and 50 cm which is 0.80 mg/L with a percentage of 86.45%. One-Way Anova test results : the p value 0.002 < 0.05 so that there is a difference in the distance of the platform height in the aeration process with the multiple platform aerator method on the decrease in iron (Fe) content. Recommendation : carry out further processing to filter the formed iron deposits.